2021
DOI: 10.1080/14992027.2021.1998838
|View full text |Cite
|
Sign up to set email alerts
|

The impact of cardiovascular diseases on hearing deterioration: a 13-year follow-up study

Abstract: Objective. To study the impact of cardiovascular diseases (CVDs) on hearing deterioration among ageing adults in a longitudinal setting. Furthermore, to describe the pure tone threshold changes at the 0.125-8 kHz frequency range over 13 years.Design. A population-based follow-up study.Study sample. A random sample of 850 adults, of whom 559 participated in the follow-up study. Otological examination, a structured interview and pure tone audiometry were conducted. Multivariate regression models were used to est… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…[40] However, not all studies investigating CV health and auditory functions found evidence in favour of the existence of a link between the two. [41][42][43][44][45] . CC-BY-NC-ND 4.0 International license It is made available under a is the author/funder, who has granted medRxiv a license to display the preprint in perpetuity.…”
Section: (Which Was Not Certified By Peer Review)mentioning
confidence: 99%
See 2 more Smart Citations
“…[40] However, not all studies investigating CV health and auditory functions found evidence in favour of the existence of a link between the two. [41][42][43][44][45] . CC-BY-NC-ND 4.0 International license It is made available under a is the author/funder, who has granted medRxiv a license to display the preprint in perpetuity.…”
Section: (Which Was Not Certified By Peer Review)mentioning
confidence: 99%
“…Some studies used ‘direct’ measures of CV health (eg, maximum amount of oxygen consumption during exercise, arterial stiffness)[34, 38] while others used ‘indirect’ measures, capturing the risk factors of CV disease (eg, self-reported history of smoking or hypertension). [43, 44] In addition, the ages and age range of the study participants were not consistent across studies (young vs older adults). [40, 42] Similarly, the hearing status of the participants and the range of included HL often varied (NH vs HL).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation